Japanese Restaurant Business Plan In New Capital Nation of Indonesia - Laksniyunita, Wanda (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
Plan the capital of Indonesia has moved being in East Kalimantan Province, providing opportunities and chances promising business-like Japanese Restaurant. This addressed for give planning and feasibility business on Japanese Restaurant in East Kalimantan Province. Japanese Restaurant This own potency big for success with superiority material standard easily available, unique taste, diverse menu, location strategic, and halal food, as well as promotional strategies through social media and delivery services. SWOT analysis shows strengths and opportunities that can be utilized, as well necessary weaknesses and threats overcome. Planning finance with capital of IDR 750,000,000 shows projection sale positive with a target of IDR 9,720,000,000 in five years, IRR 27.47%, and NPV IDR 324,787,595. With a strong marketing strategy and proper management, restaurants This expected Achieve planned sales and profit targets.